فعالية أساليب المواجهة الإيجابية في التخفيف من الضغوط المهنية - بوحنيك, عبد العزيز; كريبع, محمد; قادري, تقي الدين (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الى معرفة فعالية أساليب المواجهة الإيجابية، المستخدمة من طرف أساتذة التربية البدنية والرياضية للطور الثانوي. في التخفيف من الضغوط المهنية، ومعرفة فيما إدا كانت هناك فروق دالة إحصائيا في مستوى الضغط المهني، لدى أساتذة التربية البدنية والرياضية. تعود لاختلاف أساليب المواجهة المستخدمة، ومعرفة مستويات الضغط المهني للأساتذة. استخدم الطالب المنهج الوصفي لملائمته لطبيعة الدراسة. وتمثلت العيّنة في أساتذة التربية البدنية والرياضية للطور الثانوي لولاية ورقلة. والتي بلغ عددها 50 أستاذا. اختيرت بطريقه عشوائية بسيطة. واعتمد الطالب في هده الدراسة على مقياسين لجمع البيانات. الأول مقياس أساليب المواجهة، والثاني مقياس الضغوط المهنية. وتم استخدام برنامج اسبياس لتفريغ البيانات، ومعالجتها. وتوصل الطالب الى أن نسبة عالية من الأساتذة لديهم مستوى ضغط مرتفع، وأن هناك ارتباط بين الضغط ونوعية أسلوب المواجهة المستخدم. بحيث إدا كان الأسلوب إيجابي يكون مستوى الضغط منخفض. وإدا كان سلبيا يكون مستوى الضغط مرتفع. Abstract:The study aimed a knowing the positive facing techniques effectiveness used by Teacher sphysical education of secondary school in order to lessen the pressure exerted on in their job Also, it also aim was to find out if there is statistic differences about degree of pressure among teachers themselves which are caused by the differences in facing techniques used by the teachersof physical education The. student used the descriptive approach to suit the nature of the study, The sam. ple with dealtconsists of50secondary school teachers of sport.chosen in easy and random way, In this study, the student relied on two scales to collect data, the first is the encounteringmethods measure, and the second is the occupational stress measure, The SPSS program was used to empty data, process it, and arrive at a high percentage of 58 percent of teachers has a high pressure level, and that there is a differences of statistic significance between pressure and the quality of the confrontational method used, so that if the method is positive the pressure level is low and if it is negative the pressure level is high.
لدى أساتذة التربية البدنية والرياضية
مقال
Keywords: أساليب المواجهة؛ الضغوط المهنية; facing techniquesjob preasure ; physical education ;sport education.